Azolla pinnata mitigates pendimethalin induced immunotoxicity, oxidative stress and histopathological changes in Oreochromis niloticus - Nagwa I. S. Abu-Zahra; Mofeed Gouda; Mohamed M. Elseify; Mona E. Abass; Mohammed S. El-Gohary; Eman T. El-sokary (Scientific Reports)
Abstract Aquatic animals face multiple threats, including pesticides, heavy metals, and other environmental pollutants, risking their health and survival. Limited bioremediation studies have been conducted on the detrimental impacts of herbicides on fish. This study focused on the impact of the herbicide pendimethalin (PD) on Oreochromis niloticus and assessed the protective role of Azolla pinnata (AZ), an aquatic fern known for its phytoremediation and antioxidant properties. O. niloticus (n = 270, 34.17 ± 2.41 g) were divided into six groups in triplicate: the control (CTR), AZ-supplemented (125 g/kg diet), PD-exposed (0.5 and 1 mg PD/L), and PD-exposed with AZ supplementation (0.5 and 1 mg PD/L + AZ) groups for 28 days. PD exposure caused substantial reductions in growth performance and hematological indices (hemoglobin concentration (Hb) and red blood cell (RBC) count), with significant increases in white blood cell (WBC) count. Oxidative damage from PD exposure was evidenced by decreased superoxide dismutase (SOD) activity and acetylcholinesterase (AChE) levels, along with increased malondialdehyde (MDA) levels in hepatic and gill tissues. PD-exposed fish also presented reduced phagocytic activity (PA) and index (PI), along with decreased lysozyme activity and resistance to Pseudomonas aeruginosa infection. Additionally, hepatic and renal damage markers (AST, ALT, ALP, urea, and creatinine) and stress indicators (cortisol and glucose) were notably elevated. Severe tissue and cellular damage further highlight PD-induced damage. AZ supplementation had a protective effect, almost restoring normal growth performance, hematological parameters, and antioxidant defenses. AZ improved SOD and AChE activity and reduced MDA levels, mitigating oxidative damage. AZ also improved immune responses, restoring PA, PI, and lysozyme activity and bacterial resistance. Furthermore, AZ alleviated hepatic and renal damage, normalized stress markers, and mitigated tissue and morphological abnormalities, preserving tissue integrity. This study underscores the potential of dietary AZ supplementation (12.5%) as a growth promoter, antioxidant, and immunostimulant in aquaculture, effectively enhancing resistance to environmental toxicants and bacterial infections.